2015
DOI: 10.1515/zpch-2015-0598
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Spectra of Corannulenic Cations and Neutrals in Neon Matrices and Protonated Corannulene in the Gas Phase at 15 K

Abstract: Three absorption systems starting at 624.1, 601.2, and 590.0 nm were detected in a 6 K neon matrix following deposition of mass selected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Since this absorption feature is so broad, we are not able to identify any shift in its position as a function of the number of solvating He/D 2 units. The position of this band is in agreement with the S 3 ( 1 A) ← S 0 ( 1 A) transition of protonated corannulene that was measured using a resonant multiphoton fragmentation technique in an ion trap as a broad peak near 5150 Å 23. The width of this peak, FWHM ≈ 800 Å, can be explained by a short-lived S 3 ( 1 A) state with a lifetime of ≈2 fs, though unresolved vibrational excitations could contribute to the width making this lifetime a lower limit estimate.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Since this absorption feature is so broad, we are not able to identify any shift in its position as a function of the number of solvating He/D 2 units. The position of this band is in agreement with the S 3 ( 1 A) ← S 0 ( 1 A) transition of protonated corannulene that was measured using a resonant multiphoton fragmentation technique in an ion trap as a broad peak near 5150 Å 23. The width of this peak, FWHM ≈ 800 Å, can be explained by a short-lived S 3 ( 1 A) state with a lifetime of ≈2 fs, though unresolved vibrational excitations could contribute to the width making this lifetime a lower limit estimate.…”
Section: Resultssupporting
confidence: 86%
“…The position of this band is in agreement with the S 3 ( 1 A) ← S 0 ( 1 A) transition of protonated corannulene that was measured using a resonant multiphoton fragmentation technique in an ion trap as a broad peak near 5150 Å. 23 The width of this peak, FWHM ≈ 800 Å, can be explained by a short-lived S 3 ( 1 A) state with a lifetime of ≈ 2 fs, though unresolved vibrational excitations could contribute to the width making this lifetime a lower limit estimate. With no narrow bands originating from protonated corannulene in our measurements, it is unlikely that this system is responsible for any DIBs in this wavelength range.…”
Section: Absorption Spectra Of Protonated Corannulene Complexessupporting
confidence: 85%
See 2 more Smart Citations
“…Figure shows possible sites for protonation of corannulene. Some quantum-chemical computations of the relative energies of isomers of protonated corannulene are reported. Frash et al calculated these energies and concluded that the protonation at the hub -site has the least energy and those at the rim - and spoke -sites have energies higher by 8 and 57 kJ mol –1 , respectively …”
Section: Introductionmentioning
confidence: 99%